Sealed-Bid Auction Protocol Implementation Over Corba Architecture - Rahman, Mohammad Zahidur; Lee, Sai Peck (Malaysian Journal of Computer Science, 2001)
Verifiable secret and polynomial sharing (VSPS) scheme can be adopted in the development of a sealed-bid auction protocol for secure sealed-bid auction service. In this paper, issues related to the implementation of VSPS scheme for sealed-bid auction service is discussed. Distributed object computing over Common Request Broker Architecture (CORBA) is deployed in the protocol. To allow the access of an auction server simultaneously by more than one bidder, the concept of concurrent processing is introduced.